Disparity in education: evidence from Malaysia - Mohamed, Zunika; Said, Rusmawati (2012)
Education development has been one of the long standing policies to achieve growth, welfare and ultimately national unity in Malaysia. Besides a few studies that recorded improvement in education disparity at aggregate level, little is known about the distribution of educational achievement at a more segregated level in the country. This study investigates the disparities in education achievement in Malaysia for the period of 1995 to 2009 with respect to regional, gender and ethnic differences. The Household Income Survey (HIS) is utilized to calculate Gini education coefficient, where the head of household’s educational attainment is the unit of analysis. We found the existence of overall improvement in the education disparity over time. Gender as well as strata differences continue to be prominent while ethnic difference is very marginal. The future policy in reducing those gaps should give due consideration to reducing cost of higher level education. This will provide greater access to education for the bottom 40 per cent of the population.